Synergism of the glyphosate and saflufenacil combination for controlling hairy fleabane - Dalazen, Giliardi (2015)
In Brazil, hairy fleabane stands out among the main weeds of soybean crops, due to its aggressiveness and resistance to glyphosate. Thus, to avoid the selection of resistant populations to the glyphosate herbicide, the use of other herbicides has become critical to the management of this weed. This study aimed to evaluate the control efficiency of glyphosate and saflufenacil herbicides in hairy fleabane plants (Conyza bonariensis), as well as the type of interaction of the combination of those herbicides for controlling glyphosate-resistant hairy fleabane. A randomized blocks design, with four replications, was used. Treatments consisted of glyphosate doses (0 g ha-1; 270 g ha-1; 540 g ha-1; 1,080 g ha-1; 2,160 g ha-1; 4,320 g ha-1; 8,640 g ha-1; 17,280 g ha-1) combined with saflufenacil (0 g ha-1; 0.55 g ha-1; 1.09 g ha-1; 2.18 g ha-1; 4.37 g ha-1; 8.75 g ha-1; 17.5 g ha-1; 35 g ha-1), making six dose-response curves. A synergistic effect was observed between the glyphosate and saflufenacil herbicides for controlling the glyphosate-resistant hairy fleabane, being the mixture considered efficient for the biotype studied. Furthermore, the addition of glyphosate (540 g ha-1) to the saflufenacil herbicide (35 g ha-1) prevented the occurrence of regrowth and the dispersion of new hairy fleabane seeds, what does not occur in plants treated exclusively with saflufenacil.